Risk Factors for Fasciotomy After Revascularization for Acute Lower Limb Ischaemia - Karonen, Emil; Wrede, Axel; Acosta, Stefan (Frontiers in Surgery, 2021)
Background Acute lower limb ischaemia (ALI) is a life and limb threatening vascular emergency. Acute compartment syndrome (ACS) may develop upon revascularization. The risk of fasciotomy was hypothesized to be decreased in women due to their lower calf muscle mass. The main aim was to evaluate risk factors for fasciotomy after revascularization for ALI. Methods This is a retrospective observational study of patients undergoing revascularization for ALI between 2001 and 2018. Factors associated with outcome at 1 year in univariable analysis (p<0.1) were chosen for multi-variable analysis and expressed in Odds Ratios (OR) with 95% confidence intervals (CI). Results The median age for women (n=394) was 75 years and men (n=449) was 70 years (p<0.001). The frequency of fasciotomy was 10.0% (84/843). The median in-hospital stay was 28 versus 6 days for patients undergoing fasciotomy and not, respectively (p<0.001). In adjusted analysis, renal insufficiency (OR 1.77, 95% CI 1.04-3.01), motor deficit (OR 4.40, 95% CI 2.45-7.92), popliteal artery aneurysm thromboembolism (OR 2.26, 95% CI 1.06-4.80) and open vascular surgery (OR 3.43, 95% CI 1.97-5.98) were associated with an increased risk of fasciotomy. Female patients (OR 0.49, 95% CI 0.28-0.84) and anemia (OR 0.52, 95% CI 0.28-0.84) had a lower risk. The major amputation/mortality rate at 1-year was 27.7%; fasciotomy (OR 1.94, 95% CI 1.11-3.40), anemia (OR 1.84, 95% CI 1.24-2.73) and female gender (OR 1.44, 95% CI 1.00-2.08) were independently associated with an increased risk. Conclusions Female patients had lower rates of fasciotomies, but subsequent higher risk of major amputation/mortality, which may be attributed to inferior results of revascularization. Lower muscle mass and underdiagnosis of ACS could also explain the lower frequency of fasciotomy for female patients. Further studies are needed to better understand gender differences in presentation of ALI, revascularization results and diagnosis of ACS.